2010
DOI: 10.2174/187569210793368195
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Hepatitis B Virus Genomic Variations on Treatment Outcomes

Abstract: Infection due to hepatitis B virus (HBV) is a global public health issue. With effective treatment, it is possible to prevent disease progression to cirrhosis and hepatocellular carcinoma in chronic hepatitis B patients. Several viral factors have been documented to be associated with disease progression and treatment response, including HBV genotype and several naturally occurring HBV mutants, such as precore stop codon mutation (G1896A) and basal core promoter mutation (A1762T/G1764A). Recent studies suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Several common HBV mutant strains such as mutations in the precore (PC), core promoter (CP) and deletion mutations in the pre‐S/S genes have been associated with progressive liver disease, including cirrhosis and HCC , thus their influence on HBV treatment requires further studies. A recent review showed that half of the studies in the literature suggested the PC G1896A mutation or the basal core promoter (BCP) A1762T/G1764A mutation were associated with the response to IFN therapy . A recent study in 115 HBeAg‐positive patients who received PEG‐IFN α‐2a for 6 months indicated that the BCP A1762T/G1764A mutation was associated with a combined response defined as HBeAg seroconversion, HBV DNA levels below 20 000 IU/mL as well as normalization of ALT 6 months after therapy had stopped (OR: 8.04, 95% CI: 2.00–32.28) .…”
Section: Baseline Viral Predictorsmentioning
confidence: 99%
“…Several common HBV mutant strains such as mutations in the precore (PC), core promoter (CP) and deletion mutations in the pre‐S/S genes have been associated with progressive liver disease, including cirrhosis and HCC , thus their influence on HBV treatment requires further studies. A recent review showed that half of the studies in the literature suggested the PC G1896A mutation or the basal core promoter (BCP) A1762T/G1764A mutation were associated with the response to IFN therapy . A recent study in 115 HBeAg‐positive patients who received PEG‐IFN α‐2a for 6 months indicated that the BCP A1762T/G1764A mutation was associated with a combined response defined as HBeAg seroconversion, HBV DNA levels below 20 000 IU/mL as well as normalization of ALT 6 months after therapy had stopped (OR: 8.04, 95% CI: 2.00–32.28) .…”
Section: Baseline Viral Predictorsmentioning
confidence: 99%